Efecto de Insecticidas Biológicos, Botánicos y Químicos en el Control de Trips (Frankliniella occidentalis) en el cultivo de Rosa en la zona de Tabacundo, Provincia de Pichincha - Cuzco Coro, José Luis (2013)
The present investigation one carries out in a small property farms located in the tabacundo area, Canton Pedro Moncayo in the province of Pichincha, with the purpose of evaluating the effectiveness of six insecticides in two different dose for the trips control (Frankliniellaoccidentalis in the cultivation of the rose. You identifies the most appropriate insecticide with their respective dose and you also analyzes economically the treatments. As genetic material you uses the variety of pink Freedom. You applies the design of complete blocks at random (DBCA), with 12 treatments and three repetitions. All the variables were subjected to the Analysis of Variance (ADEVA) using the test Tukey to 5% effectiveness of the insecticides, plant height to the 30,60 days was evaluated of initiate the rehearsal and to the crop, long and shaft diameter, height and button diameter, I number of exportable and national shafts and the economic analysis. The conclusions were The biggest control for the plague trips they were the chemical insecticides especially the treatment T12 with an average of 0 - 1 trips/botón, in the variable plant height, long and shaft diameter, height and button diameter one could observe that there was not difference statistic since all the insecticides they worked mainly in the control...........